2017
DOI: 10.1007/s00395-017-0659-5
|View full text |Cite
|
Sign up to set email alerts
|

Periostin in cardiovascular disease and development: a tale of two distinct roles

Abstract: Tissue development and homeostasis are dependent upon the concerted synthesis, maintenance, and degradation of extracellular matrix (ECM) molecules. Cardiac fibrosis is now recognized as a primary contributor to incidence of heart failure, particularly heart failure with preserved ejection fraction, wherein cardiac filling in diastole is compromised. Periostin is a cell-associated protein involved in cell fate determination, proliferation, tumorigenesis, and inflammatory responses. As a non-structural componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 502 publications
1
68
1
Order By: Relevance
“…Experiments with tunable hydrogels of different stiffness (using methacrylated gelatin, collagen, and other materials) have demonstrated the importance of mechanical factors modulating CF phenotypes in 3D culture models (Hutson et al, 2011;Sadeghi et al, 2017). The non-structural ECM protein periostin is a target of transforming growth factor-β1 (TGF-beta) signaling via canonical pathways in the heart, where this protein is found in the developing myocardium playing a profibrogenic role, but not in the adult heart at baseline (Landry et al, 2017). Periostin expression followed the downregulation found for alpha-SMA in CF-only spheroids, but not in 3D co-cultures.…”
Section: Cytoarchitecture Gene Expression and Maturationmentioning
confidence: 99%
“…Experiments with tunable hydrogels of different stiffness (using methacrylated gelatin, collagen, and other materials) have demonstrated the importance of mechanical factors modulating CF phenotypes in 3D culture models (Hutson et al, 2011;Sadeghi et al, 2017). The non-structural ECM protein periostin is a target of transforming growth factor-β1 (TGF-beta) signaling via canonical pathways in the heart, where this protein is found in the developing myocardium playing a profibrogenic role, but not in the adult heart at baseline (Landry et al, 2017). Periostin expression followed the downregulation found for alpha-SMA in CF-only spheroids, but not in 3D co-cultures.…”
Section: Cytoarchitecture Gene Expression and Maturationmentioning
confidence: 99%
“…The extracellular matrix is an essential component of organ structure and function and is dynamically regulated by fibroblasts under normal conditions (Lu et al, 2014). As an extracellular matrix protein, Periostin plays a vital role in the development of various organ tissues (Izuhara et al, 2016;Landry et al, 2018). In an animal experiment, Liu et al (2017) found that Periostin is upregulated in brain tissues after subarachnoid hemorrhage, leading to early brain injury and that the underlying mechanism may be related to the activation of downstream signaling pathway and the interaction of cell-adhesin-C.…”
Section: Discussionmentioning
confidence: 99%
“…Periostin, which is an extracellular matrix protein involved in normal bone remodeling and biology of different cancer cell growths and metastases, is overexpressed in oral, thyroid, breast and gastric cancers (Bonnet et al, 2016;Izuhara et al, 2016;Landry et al, 2018;Lu et al, 2014). Moreover, Siriwardena et al (2006) showed that Periostin is abnormally elevated in oral squamous cell carcinoma and promotes the metastasis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Periostin also plays an important role in diseases associated with the cardiovascular and central nervous systems. In cardiac diseases, periostin has been demonstrated to activate the integrin-associated p38, FAK, and phosphoinositide 3kinase/Akt and Wnt/β-catenin signaling cascades in fibroblasts and vascular smooth muscle cells [49]. In addition, TGF-β in association with the subunits of the αv integrin is released as a result of mechanical stress, rendering the integrins available for interaction with periostin, which in turn may initiate a feed-forward loop of periostin signaling [49].…”
Section: Periostin In Various Disordersmentioning
confidence: 99%
“…In cardiac diseases, periostin has been demonstrated to activate the integrin-associated p38, FAK, and phosphoinositide 3kinase/Akt and Wnt/β-catenin signaling cascades in fibroblasts and vascular smooth muscle cells [49]. In addition, TGF-β in association with the subunits of the αv integrin is released as a result of mechanical stress, rendering the integrins available for interaction with periostin, which in turn may initiate a feed-forward loop of periostin signaling [49]. In a rat model of acute myocardial infarction, overexpression of full-length periostin was reported to be associated with ventricular dilatation along with collagen deposition, while the splicing variants of periostin (a variant of periostin lacking exon 17 and another one lacking exons 17 and 21) were reported to be associated with myocardial repair [50].…”
Section: Periostin In Various Disordersmentioning
confidence: 99%